The Potential Role of hsa_circ_0005505 in the Rupture of Human Intracranial Aneurysm - Chen, Xin; Yang, Shuzhe; Yang, Junhua; Liu, Qingyuan; Li, Maogui; Wu, Jun; Wang, Hao; Wang, Shuo (Frontiers in Molecular Biosciences, 2021)
Objective: Recently, abundant numbers of studies have revealed many functions of circular RNAs in multiple diseases, however, the role of circular RNA in the rupture of human intracranial aneurysm is still unknown. This study aims to explore the potential functions of circular RNA in the rupture of human intracranial aneurysms. Methods: The differentially expressed circular RNAs between un-ruptured intracranial aneurysms (n=5) and ruptured intracranial aneurysms (n=5) were analyzed with the Arraystar human circRNAs microarray. Quantitative real-time PCR (qPCR) was used to verify the results of the circRNA microarray. The role of circular RNA in intracranial aneurysm rupture was assessed in vitro. MTT assay, CCK-8 assay, Caspase3/7 assay, assay of cell apoptosis and Celigo wound healing was conducted to evaluate the relationship between circular RNA and the rupture of human intracranial aneurysms. Results: A total of 13175 circRNA genes were detected. Among them 63 circRNAs upregulated and 54 circRNAs downregulated significantly in ruptured intracranial aneurysms compared with un-ruptured intracranial aneurysms (p<0.05 Fold Change>1.5). 5 upregulated circRNAs were selected for further study (hsa_circ_0001947, hsa_circ_0043001, hsa_circ_0064557, hsa_circ_0058514, hsa_circ_0005505). The results of qPCR showed only hsa_circ_0005505 significantly upregulated (P<0.05). The expression of hsa_circ_0005505 was higher in ruptured intracranial aneurysm tissues. And our in vitro data showed that hsa_circRNA_005505 promotes the proliferation the migration and apoptosis of vascular smooth muscle cell. Conclusions: This study revealed an important role of hsa_circ_0005505 in the proliferation, migration and apoptosis of vascular smooth muscle cell, and indicated that hsa_circ_0005505 may associate with the pathological process of intracranial aneurysms.